AN ANALYSIS ON GRADUATES’ PERCEPTIONS TOWARDS TEST OF ENGLISH AS A FOREIGN LANGUAGE (TOEFL) - Ermawan, Ery; Arifin, Zainal; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: This is a case study to the graduates of English Education Study Program of Teacher Training and Education Faculty, Tanjungpura University Pontianak. This study aims to know the graduates perceptions towards Test of English as a Foreign Language (TOEFL) and also gathers data about the graduates’ TOEFL score attaintment in academic year 2012 and 2013. There were ten respondents who involved in this study. The data were collected through interviews and documentary methods. The research findings showed that from ten respondents of interview whose score above the standard, nearly all the respondents with those good scores regard TOEFL positively and support this language policy. The respondents even conveyed the benefits of TOEFL including tips to pass the test. Keywords: TOEFL, Perception, Graduate Abstrak: Penelitian ini merupakan penelitian studi kasus kepada alumni dari Program Studi Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, Universitas Tanjungpura Pontianak. Penelitian ini bertujuan untuk mengetahui persepi para alumni Program Studi Bahasa Inggris terhadap TOEFL dan juga untuk mengumpulkan data-data tentang pencapaian skor TOEFL oleh para alumni pada tahun akademik 2012 dan 2013. Terdapat 10 responden yang terlibat dalam penelitian ini. Data dari penelitian ini dikumpulkan melalui interview dan metode documentary. Hasil penelitian menunjukkan bahwa dari 10 responden dalam interview yang semuanya memiliki skor TOEFL diatas skor standar, hampir keseluruhannya memandang TOEFL dengan positif dan mendukung kebijakan bahasa ini. Para responden bahkan menyampaikan beberapa manfaat dari TOEFL termasuk tips-tips untuk lulus tes tersebut. Kata Kunci: TOEFL, Persepsi, Alumni